(10) When using substitution to solve this system of equations, what is the result of the first step? Eq#1 y = 6x + 3 Eq#2 x + 2y = 5
![10 When using substitution to solve this system of equations what is the result of the first step Eq1 y 6x 3 Eq2 x 2y 5 class=](https://us-static.z-dn.net/files/dec/384e2d75e7692c7ae86a34479b07a08a.png)
Given data:
The first equation given is y = 6x + 3.
The second equation given is x + 2y = 5.
Subsitute (6x+3) for y in second equation.
[tex]x+2(6x+3)=5[/tex]Thus, the first option is correct.